1999
DOI: 10.1007/s002689900606
|View full text |Cite
|
Sign up to set email alerts
|

Are There Indications for Palliative Resection in Pancreatic Cancer?

Abstract: Obertop, H. (1999). Are there indications for palliative resection in pancreatic cancer ? World journal of surgery, 23, 954-959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
0
20
1
5
Order By: Relevance
“…These findings are in contrast to other authors [18,16] who could not find a difference in perioperative morbidity between bypass surgery and resection, however, as previously mentioned, in these analyses, so-called palliative resections included patients with microscopical tumor remnants (R1).…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…These findings are in contrast to other authors [18,16] who could not find a difference in perioperative morbidity between bypass surgery and resection, however, as previously mentioned, in these analyses, so-called palliative resections included patients with microscopical tumor remnants (R1).…”
Section: Discussioncontrasting
confidence: 80%
“…In our opinion, tumor debulking it is not an option in the treatment of pancreatic cancer; however, there is an ongoing debate about palliative pancreaticoduodenectomy since this procedure is associated with limited mortality in experienced centers and may lead to better pain control [16,18]. Nieveen van Dijkum et al compared quality of life after bypass surgery and pancreaticoduodenectomy in patients with potentially resectable tumors and found that quality of life does not differ significantly after bypass and resection [21].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Die vorliegenden Studien zeigen, dass eine palliative Resektion mit vergleichbarer Morbidität und Mortalität wie eine Bypass-Operation durchgeführt werden kann und unter Umständen zu einer verlängerten Überlebenszeit führt [14,24,26,28,35]. Aufgrund der niedrigen Mortalität bei Pankreasresektion in spezialisierten Zentren sollte die Frage, ob Patienten von einer palliativen Pankreatikoduodenektomie profitieren, in randomisierten kontrollierten Studien beantwortet werden.…”
Section: Pankreaschirurgieder Chirurg Als Wesentlicher Prognostischerunclassified